2021
DOI: 10.1016/j.compstruct.2021.114210
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and finite element analysis of the impact response of agglomerated cork and its intraply hybrid flax/basalt sandwich structures

Abstract: The material from this source included in this thesis is not singled out with typographic means and references and is included in Chapters 2 and 4.➢ "Cork core sandwich structures: static and dynamic response" Claudia Sergi, Jacopo Tirillò,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 195 publications
0
2
0
Order By: Relevance
“…More recently, Sergi et al [29] tested the resistance of sandwich structures containing cork agglomerates as the core material. They found that a higher density resulted in greater resistance and less maximum displacement, and the cork agglomerates showed an excellent capacity for dimensional recovery after compression.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Sergi et al [29] tested the resistance of sandwich structures containing cork agglomerates as the core material. They found that a higher density resulted in greater resistance and less maximum displacement, and the cork agglomerates showed an excellent capacity for dimensional recovery after compression.…”
Section: Introductionmentioning
confidence: 99%
“…For this application, the impact and flexural behaviour of sandwich is highly inspected [20][21][22][23][24]. The majority of the bio-based composite sandwich materials and structures developed so far have been indeed tested under monotonic, dynamic, fatigue or impact loading conditions [20,[25][26][27][28][29][30][31][32][33][34][35][36][37]. There is a certain lack of data and knowledge in open literature concerning the long-term behaviour, in particular creep bending under hygrothermal conditions.…”
Section: Introductionmentioning
confidence: 99%